One-Pot Synthesis of Acidic Mesoporous Activated Carbon Obtained from Yerba Mate Twigs as Suitable Catalyst for the Production of Levulinic Ester Biofuel Additives - Alvear Daza, John Jairo (2024)
A series of activated carbons (YMBC) obtained from yerba mate twig residue (YMT) were prepared by chemical (H3PO4) and thermal activation. Five materials were synthesized, varying the carbonization temperature (400–600 °C under N2 atmosphere) and H3PO4:YMT ratio (60–80 wt%). They were physicochemically and texturally characterized by SEM-EDX, BET, FT-IR, and 31P MAS-NMR. Potentiometric titration with the n-butylamine technique was used to evaluate their acidic properties. The materials exhibited a high specific surface area (572 m2 g−1 < SBET < 1031 m2 g−1) and mesoporosity (67% < Smeso/SBET < 93%). The results showed that the acid strength and the number of acid sites increased with the H3PO4:YMT ratio and decreased with the calcination temperature increment. The FT-IR and 31P characterization revealed the presence of Hn+2PnO3n+1 species firmly (via P-O-C linkages) and loosely attached (by electrostatic interaction). The latter were successfully removed by refluxing the material in water or n-propanol. The optimal reaction conditions were applied to the synthesis of other levulinic acid esters using YMBC-500-70NP as a catalyst. Furthermore, the effective separation of the product combined with the use of a recyclable catalyst resulted in a clean and environmentally friendly strategy for the synthesis of alkyl levulinates, bioproducts of relevance to the biorefinery industry, which can be applied as fragrances, flavoring agents, as well as fuel additives.